(untitled) (Revista de Ciências Agroveterinárias, 2006)
The objective of this study was to determine the biological parameters of Urbanus acawoios (Willians, 1926) (Lepidoptera: Hesperiidae) in Phaseolus vulgaris cultivars. The ambient temperature during the experiment was 21,710C + 2,020C. The Urbanus acawoios caterpillars presented five instars in the studied cultivars. The Urbanus acawoios caterpillars fed with Carioca Precoce’s cultivar didn’t complete their life cycle. The Goiano Precoce and Emgopa Ouro 201 cultivars were more favorable to the development of Urbanus acawoios.